Stereoselective approach to indolizidine and pyrrolizidine alkaloids: total synthesis of (-)-lentiginosine, (-)-epi-lentiginosine and (-)-dihydroxypyrrolizidine - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (Organic & Biomolecular Chemistry, 2014)
A simple and highly efficient approach to hydroxylated pyrrolizidine and indolizidine is developed from an aldehyde as a starting material using organocatalytic and asymmetric dihydroxylation reactions as key steps. Its application to the total synthesis of (-)-lentiginosine, (-)-epi-1,2-lentiginosine and (-)-dihydroxypyrrolizidine is also reported.